Language contestation in the virtual linguistic landscape of the official website of Malang City: Indonesian and Javanese Dialects - Isnaini, M.; Wurianto, Arif Budi; Hieu, Ho Ngoc (Universitas Ahmad Dahlan, 2026)
This study examines language contestation in the virtual linguistic landscape (VLL) of the official website of Malang City Government, focusing on the interaction between Indonesian and Javanese dialects. While previous studies emphasize the dominance of national languages in digital governance, this study critically interrogates whether such dynamics represent contestation, coexistence, or symbolic marginalization. Using a concurrent mixed-methods design, data were collected from 55 indexed web pages through systematic content analysis, supported by policy documentation and semi-structured interviews with website administrators (n = 3). The analysis integrates linguistic distribution, language style, and communicative function within a VLL framework. The findings reveal that Indonesian overwhelmingly dominates administrative and informational functions, while Javanese dialects appear in limited symbolic forms, such as service names and cultural expressions. Rather than indicating active contestation, this pattern reflects a hierarchical linguistic order shaped by institutional norms, regulatory constraints, and digital governance practices. This study contributes theoretically by reconceptualizing “language contestation” in digital institutional spaces as structured hierarchy rather than direct competition. Practically, it highlights the need for more functional integration of regional languages in digital governance to support linguistic diversity beyond symbolic representation.